Heat treatment of grain-processing facilities: gauging effectiveness against select life stages of Tribolium castaneum (Herbst) using bioassays and a thermal death kinetic model - Bingham, Aaron C. (Kansas State University, 2014)
During heat treatment, the ambient temperature of grain-processing facilities is raised to 50-60°C for at least 24 hours to manage stored-product insects. Young larvae (first instars) of the red flour beetle, Tribolium castaneum (Herbst), are the most heat tolerant stage at 50-60°C. A thermal death kinetic (TDK) model predicted survival of T. castaneum young larvae exposed to six constant elevated temperatures between 42 and 60ºC. The model is based on logarithmic survival of T. castaneum as a function of time and logarithmic reduction in larval survival as a function of temperature. The model was validated with 12 independent temperature datasets collected during heat treatments of pilot-scale and commercial grain-processing facilities. Young larval survival in plastic boxes/vials with flour was used to validate model predictions. The heating rate to 50°C from the ambient among the 12 datasets ranged from 0.9-7.8°C/h. Mean absolute deviations between observed and predicted larval survival for 10 of the 12 datasets ranged from 2.1-11.4%; it was 16.2 and 18.3% for two other datasets. The TDK model can be used to predict survival of young larvae of T. castaneum based on time-dependent temperature profile obtained at any given location during heat treatment of grain-processing facilities. In three commercial grain-processing facilities heat treatments were conducted for 24-27.7 hours using forced-air gas heaters. Temperatures attained and survival of 20 eggs, 20 young larvae, and 20 adults of T. castaneum in bioassay vials at various locations were determined. Across all three facilities, 5 out of 2720 adults in 136 vials, 1 out of 960 young larvae in 48 vials, and 0 out of 1760 eggs in 88 vials were alive at the end of the heat treatment. In each facility, the time in hours for 1% predicted survival of T. castaneum young larvae was positively related to how quickly temperatures reached 50°C, and negatively related to rate of heating to 50°C from the ambient, time above 50°C in hours, and the maximum temperature. Bioassays with T. castaneum life stages and the TDK model can be used to gauge effectiveness of facility heat treatments.
Keywords: Heat treatment; Red flour beetle; Thermal death kinetic model; Tribolium castaneum; Agriculture, General (0473)